FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Angel Mardenia Giovanni; Sri Daryanti; Juni Simina (Jurnal Paradigma Akuntansi, 2026)
The main objective of this study is to identify and analyze the effect of company size, leverage, profitability, and sales growth on firm value in primary consumer sector companies, the consumer non-cyclicals sub-sector, which are listed on the Indonesia Stock Exchange (IDX). The population for this research is 2019 – 2021 using 104 data consisting of 44 companies in the primary consumer sector, the consumer non-cyclicals sub-sector, which have been selected through a purposive sampling method. The software used to process the data in this study is SPSS 22. The results of this study indicate that company size has no significant and negative effect on firm value, leverage has a significant and positive effect on firm value, profitability has a significant and positive effect on firm value, and Sales growth has a significant and negative effect on firm value.